¿Sabías que? - Alvarado Vázquez, Marco A.; Salcedo Martínez, Sergio M.; Vargas López, Victor Ramón (Universidad Autónoma de Nuevo León, 2024)
Se exponen distintos “datos curiosos” e interesantes sobre ciencia y tecnología.